Charge transfer doping in functionalized silicon nanosheets/P3HT hybrid material for applications in electrolyte-gated field-effect transistors. Issue 27 (29th June 2018) - Lyuleeva, Alina; Holzmüller, Philipp; Helbich, Tobias; Stutzmann, Martin; Brandt, Martin S.; Becherer, Markus; Lugli, Paolo; Rieger, Bernhard
Abstract : This work introduces microwave-assisted thermal hydrosilylation reaction for the functionalization of silicon nanosheets, leading to the successful electronic interaction within SiNS–substrate/P3HT-based hybrid blends. Abstract : Hydrogenated two-dimensional (2D) silicon nanosheets (SiNSs), also called silicanes, have lateral sizes ranging from hundreds of nanometers to several micrometers and heights in the nanometer range. Due to the sp 3 -hybridization and the H-termination, SiNSs possess a band gap, show green photoluminescence and can be functionalized according to the subsequent needs of desired applications. Thus, they are suitable for industrial processing techniques, which involve incorporation in nanocomposites and application in novel nano-silicon based technology. In this work, we present the modification of the silicane surface with various molecules, using a microwave-reactor system for reproducible microwave-assisted thermal hydrosilylation. Subsequently, the modified SiNSs are used for blend formation with the semiconducting workhorse polymer poly(3-hexylthiophene) (P3HT). This hybrid nanocomposite acts as sensitive thin film for electrolyte-gated field-effect-transistors fabrication. The functionalization of the nanosheets can be varied and adjusted to the characteristics of the polymer, to prepare homogeneous hybrid systems. In this regard, thiophene-based conjugated substrates are grafted on the SiNS surface for improved film homogeneity and electrical performance. The fabricated devices are furthermore compared with the silicon-based molecular analogues (polysilanes), as well as with 0D silicon nanocrystals (SiNCs), confirming the superior performance of SiNSs. To elucidate the performance improvement, electron paramagnetic resonance (EPR) measurements are presented, demonstrating charge transfer doping in the hybrid material of P3HT and SiNSs. The corresponding mechanism for the electronic transportation is described in this work.